HIF-1α in Osteoarthritis: From Pathogenesis to Therapeutic Implications - Zeng, Chu-Yang; Wang, Xi-Feng; Hua, Fu-Zhou (Frontiers in Pharmacology, 2022)
Osteoarthritis is a common age-related joint degenerative disease. Pain, swelling, brief morning stiffness, and functional limitations are its main characteristics. There are still no well-established strategies to cure osteoarthritis. Therefore, better clarification of mechanisms associated with the onset and progression of osteoarthritis is critical to provide a theoretical basis for the establishment of novel preventive and therapeutic strategies. Chondrocytes exist in a hypoxic environment, and HIF-1α plays a vital role in regulating hypoxic response. HIF-1α responds to cellular oxygenation decreases in tissue regulating survival and growth arrest of chondrocytes. The activation of HIF-1α could regulate autophagy and apoptosis of chondrocytes, decrease inflammatory cytokine synthesis, and regulate the chondrocyte extracellular matrix environment. Moreover, it could maintain the chondrogenic phenotype that regulates glycolysis and the mitochondrial function of osteoarthritis, resulting in a denser collagen matrix that delays cartilage degradation. Thus, HIF-1α is likely to be a crucial therapeutic target for osteoarthritis via regulating chondrocyte inflammation and metabolism. In this review, we summarize the mechanism of hypoxia in the pathogenic mechanisms of osteoarthritis, and focus on a series of therapeutic treatments targeting HIF-1α for osteoarthritis. Further clarification of the regulatory mechanisms of HIF-1α in osteoarthritis may provide more useful clues to developing novel osteoarthritis treatment strategies.